Cubisti : Cubismo - Eyerman, Charlotte (Milano : SKIRA, 2013)
Picasso, Pablo ; Braque, Georges ; Gleizes, Albert ; Marchand, Jean ; Metzinger, Jean ; Picabia, Francis ; Derain, André ; Villon, Jacques ; Bell, Vanessa ; Hartley, Marsden ; Herbin, Auguste ; Lewis, Wyndham ; Severini, Gino ; Gutfreund, otto ; Weber, Max et al.
Cubisti Cubismo, Complesso Momumentale del Vittoriano, Roma, 8 marzo - 23 giugno 2013
boek